Ten gamat species in Malaysia’s seawaters for health-based industries - Kamarudin, Kamarul Rahim; Hashim, Ridzwan (2012)
Gamat the most well known sea cucumber species by the Malaysians especially in Peninsular Malaysia or West Malaysia. Gamat is a local name for all species of family S=chopodidae. Genera of S&chopus and Thelenota are the wo members of family S=chopodidae which can be found in Malaysia’s seawaters e.g. S&chopus horrens Selenka, 1867 and Thelenota anax H.L. Clark, 1921. For years, gamat has become popular as the main ingredient in the traditonal medicine industry in Peninsular Malaysia. Gamat has been exploited for its body fluid extracts i.e. air gamat and lipid extracts i.e. minyak gamat. The Langkawi Archipelago and Pangkor Island are the main produc=on sites of air gamat and minyak gamat. In line with the development of science and technology, modern-‐formularised gamat-‐based products sold by Malaysia’s companies e.g. Gamat eMas Sdn. Bhd., Nur Af Enterprise, Nutrifes Food & Beverages Industries Sdn. Bhd., and Luxor Network Sdn. Bhd. are also available in the markets. S. horrens or Gamat Emas has been used as the main ingredient, and the availability of other potential gamat species will offer great alternatives to avoid its depletion and then extinction